Advantages of using T1-mapping in cardiac magnetic resonance imaging in patients with acromegaly - Alina A. Almaskhanova; Konstantin V. Melkozerov; Elena G. Przhiyalkovskaya; Natalia V. Tarbaeva; Anastasya Y. Korneluk; Raisa S. Kosharnaia; Victor Y. Kalashnikov; Zhanna E. Belaya; Galina A. Mel'nichenko; Natalia G. Mokrysheva (Терапевтический архив)
Aim. To determine the incidence of interstitial myocardial fibrosis (MF) in acromegaly, which leads to the development of cardiac arrhythmias and conduction disorders.